Blended Learning Effectiveness: A Quasi-Experimental Study on Students’ ESP Achievement - Naajihah Mafruudloh; Nur Mafissamawati Sholikhah; Rahima Fitriati (EDULANGUE, 2022)
Blended Learning, a mixture of face-to-face (FTF) and online learning, has gained its popularity in the English language teaching context. However, examining its efficacy in English for Specific Purposes (ESP) remains scares. To fill this gap, this study implemented BL in an Indonesian ESP classroom and examined its effect on students’ learning attainment and the challenges they encountered. Drawing on the data garnered from pre- and post-tests, it was unveiled that using BL promoted the students’ learning outcomes given the statistical evidence was 0.000 which means lower than 0.05. Three main challenges of blended learning implementation were also identified, namely limitation of proper media, time allocation, and instructional aspect. This study incapsulates that the use of Blended Learning could promote students’ English language skills. This study recommends that future studies be carried out involving more participants and more varied ESP classes to gain more robust results.